The Link Road Design of Jalan Plupuh Tanon And Jalan Gabugan Section 1, Sragen Indonesia - Elizabeth Olivia Joice; Andri Irfan Rifai; Mohamad Taufik (International Journal Labs, 2022)
Easy community life, both in terms of economic, social, educational, and others, is the purpose of designing and constructing access roads or connecting roads. In addition, road design must consider safety aspects to achieve safe, balanced, and sustainable road performance. In this study, a manual horizontal alignment road design was carried out to link the road of Jalan Plupuh Tanon and Jalan Gabugan Sragen Section 1 from STA 0 + 000 to STA 2 + 257,221 with the planning of three bend points guided by Highway Design Standard of Indonesia 2021. Primary data in the form of coordinates and contours are taken from Google Earth and the Global Mapper. The design starts by managing primary data and calculating the elements that make up the horizontal alignment so that a road with a design speed of 30 km/h is obtained, the value of e = 8%, and a radius of 200 m. Three horizontal alignment points use a Spiral-Circle-Spiral (SCS) arch with an intermediate curve (Ls) value of 38 m and a circular arch (Lc) of 44.229 m, respectively.